Edukasi Pembuatan Pembukuan Keuangan Sederhana Menggunakan Aplikasi Digital Pada Usaha Desa Ambulu - Oktavia, Ade Ririn; Rivayanti, Tesa Putri; Fadjrin, Yuan Wikani; Handayani, Wiwik (Lembaga Penelitian, Pengabdian kepada Masyarakat dan Publikasi Universitas Bhayangkara Jakarta Raya, 2023)
Ambulu is one of the villages located in Sumberasih Subdistrict, Probolinggo Regency. Ambulu Village has 5hamlets consisting of Damaran Hamlet, Talang Hamlet, Krajan Hamlet, Central Hamlet and Kramat Hamlet.Based on the village's main data in 2022, this village has approximately 100 Micro, Small and MediumEnterprises engaged in fisheries, food, fashion, and also design. Micro, Small and Medium Enterprises (MSMEs)are one of the mainstays of the economy in Indonesia. However, there are still many MSMEs that do not usefinancial records to support their businesses. One of the reasons why MSMEs do not do bookkeeping is becausethey are considered difficult and not important. As a result, the development of the business, especially regardingfinancial results, cannot be clearly known. Therefore, the background of this socialization activity was held withthe aim that MSME actors in Ambulu Village, Sumberasih District were able to increase their knowledge and howto apply the practice of recording simple financial bookkeeping so that MSME actors knew the financial conditionof their business. The implementation method used is door to door by starting with a simple explanation offinancial bookkeeping records, followed by application and then ending with a discussion and question andanswer session. Based on the results of this activity, 75% of participants already knew the importance of financialmanagement, recording, and financial reporting. From the results of the socialization of the importance of makingsimple financial bookkeeping can increase insight as well as knowledge of making business financial bookkeeping.